Advanced Oxidative Processes: fundamentals and environmental application - Fioreze, Mariele; Santos, Eliane Pereira dos; Schmachtenberg, Natana (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The Advanced Oxidation Processes (or Advanced Processes Oxidation) known by the acronym POA’s are processes which rely on the generation of free radicals, especially the hydroxyl radical (∙OH), which has high oxidizing power and can promote the degradation of various compounds pollutants efficiently. These processes have gained great attention due to the increasing complexity and difficulty in treating wastewater, which has been the reason for searching for new methodologies aimed at remediation of such wastes. Therefore, the present study aimed to relate four treatment methodologies of Advanced Oxidation: H2O2 processes involving, systems Fenton and Photo-Fenton, Heterogeneous Photocatalysis and systems based on the use of ozone. The present review describes the main principles of these processes and discusses mechanisms of degradation of organic pollutants. The main advantages of using these processes is in its specificity and can be used to degrade substrates of any chemical nature, the possibility of employment to degrade pollutants whose concentration is very low (μg L-1) and not waste. Furthermore, some drawbacks are noted, such costs can be high and the formation of reaction byproducts.